KEBERLANJUTAN USAHATANI MANGGIS PROGRAM SERTIFIKAT PRIMA DI KECAMATAN KOTA AGUNG KABUPATEN TANGGAMUS - Biha Melati Sari; Bustanul Arifin; Yaktiworo Indriani (Lampung University, 2018)
This research aims to analyze the performance of mangosteen farming and certification benefits of sustainable mangosteen farming development in terms of economic, social, and environmental aspects. The location of the research is decided purposely in Terdana, Kota Agung, Tanggamus District. The samples of this research are 54 farmers whose products have been certified by prima. The performance of mangosteen farming is assessed by R / C ratio. The results showed that the performance of mangosteen farming in terms of R / C ratio per-ha was 6.91; it meant that each cash cost incurred by farmers of Rp1.00 then the farmers would receive revenue of Rp6.91 (could provide benefits on economical aspects). Prima Certification Program of mangosteen farming in Terdana, Kota Agung, Tanggamus district was quite sustainable in economic, social, and environmental aspects, in which sustainability index were 67.90; 71.02 and 72.82Key words: farm income , mangosteen, prima certification, sustainability